'I want to ride my bicycle': delimiting cyclist typologies. Issue 8 (4th May 2017) - Brey, Raúl; Castillo-Manzano, José I.; Castro-Nuño, Mercedes
ABSTRACT: Based around fieldwork in Seville (Spain), our article provides an empirical analysis with the aim of determining whether different typologies of cyclists exist depending on the type of bicycle for urban commuting (public bicycle/private bicycle). Our findings show that users of public bicycles are predominantly male, young, with a high level of education, and basically use the public bicycle for subsistence trips due to its easy intermodality; while private bicycle riders are mainly females who regularly make nonsubsistence trips and prefer a more flexible bicycle for their daily needs.